PERANCANGAN PENYEBARAN DAYA PADA SINGLE-MODE FIBER DENGAN MENGGUNAKAN BAHAN LITHIUM NIOBATE (LiNbO3) DAN PARAFIN (C20H42) - Teodora Maria Meliati Sinaga; Saktioto '; Iwantono 'PERANCANGAN PENYEBARAN DAYA PADA SINGLE-MODE FIBER DENGAN MENGGUNAKAN BAHAN LITHIUM N (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Optical switch represents good technology components used in many application especially in communication. Optical switch is different from conventional one having many advantageous. Single mode fiber optics is used as a waveguide for propagating the power of Laser Source and detected by power meter. The design is started by connecting single mode fiber optics to the source and detector. The voltage source is measured  corresponding to power meter detector. The result shows that the lowest output power is detected from the paraffin of -39,28 dBm and fiber the output power is -12,67 dBm. The maximum input voltage is 3200 Volt and output voltage is 1061 Volt for optical fiber and the lowest electric field obtained is 223,2 x 10−11A/m2. The current density is 223,2 x 10−11 A/m2  for paraffin with 500 μm in diameter. The output voltage for paraffin 1032 Volt, the electric field of 412,8 x 104 V/m and current densityis 412,8 x 10−11 A with 250 μm in diameter.